The European social model under pressure: liber amicorum in honour of Klaus Armingeon - Careja, Romana; Emmenegger, Patrick; Giger, Nathalie (Springer Vieweg in Springer Fachmedien Wiesbaden GmbH, 2020)
Intro -- Table of Contents -- Tabula Gratulatoria -- 1 The European social model under pressure: Introduction -- Introduction -- Brief overview of Klaus Armingeon's career and scholarly contribution -- This volume -- References -- Part I Transformation of Neo-Corporatism -- 2 Neo-corporatism and the responsiveness of democracy -- 1 Introduction -- 2 Interest groups, party politics and the responsiveness of democratic policy-making -- 3 Neo-corporatism and the responsiveness of democratic policy-making -- 4 The potential contribution of corporatist institutions and practices to mitigating political inequalities -- 5 The dangers of aggravating political inequalities and non-responsiveness -- 6 Conclusions -- References -- 3 Social concertation in Europe during the Great Recession: A fsQCA-study of social partner involvement -- 1 Introduction -- 2 From corporatism to social concertation -- 3 Hypotheses on explanatory factors for social concertation since 2008 -- 3.1 Economic factors -- 3.2 Power resources approach and labour relations -- 3.3 Political institutions and actors -- 4 Fuzzy Set Qualitative Comparative Analysis -- 4.1 Calibrating the outcome: social concertation -- 4.2 From indicators to fuzzy set conditions -- 5 Necessary and sufficient conditions for social concertation -- 5.1 Necessary conditions for social concertation -- 5.2 Sufficient conditions for social concertation -- 6 Conclusion -- References -- 4 Transformations of Swiss neo-corporatism: From pre-parliamentary negotiations towards privileged pluralism in the parliamentary venue -- 1 Introduction -- 2 Declining role of pre-parliamentary negotiations and revalorization of the Parliament: A challenge for Swiss neo-corporatism? -- 3 Seats in pre-parliamentary committees -- 4 Focus on pre-parliamentary committees in the economic and social policy domains.
Description based on publisher supplied metadata and other sources
Keywords: Festschrift; Aufsatzsammlung; Wohlfahrtsstaat; Sozialstaat; Europa